Geochemical Characteristics of Basalt in the Northern Taopa Area, Parigi Moutong Regency, Central Sulawesi - Magfira, Sri Wanda; Asrafil, Asrafil; Puspita, Riska (Universitas Negeri Gorontalo, 2026)
This study analyzes the geochemical characteristics of basaltic rocks in the Northern Taopa (Taopa Utara) area, Parigi Moutong Regency, Central Sulawesi, to constrain magma affinity, magmatic series, and tectonomagmatic setting. Although Central Sulawesi records complex arc–oceanic interaction, the major-element geochemistry of basalts from Northern Taopa has remained poorly documented. Petrographic observations and X-ray fluorescence (XRF) major-oxide analyses were conducted on four representative samples (ST10, ST19, ST24, and ST36). Petrographic analysis shows that all samples have a hypocrystalline–porphyritic texture with plagioclase, clinopyroxene, olivine, and opaque minerals set in a microlitic groundmass. Major-oxide compositions are characterized by SiO2 48.85–50.65 wt% and total Fe2O3 12.89–13.11 wt%, consistent with mafic basalt. On the total alkali–silica diagram the samples plot in the basalt field and display low total alkalis (Na2O+K2O 1.11–2.11 wt%) and very low K2O (0.039–0.051 wt%), indicating a low-K subalkaline affinity. AFM relations show relative Fe enrichment and place the samples within the tholeiitic series. Tectonic discrimination using TiO2–P2O5–MnO (TiO2 0.98–1.06 wt%; P2O5 0.405–0.427 wt%; MnO 0.208–0.276 wt%) suggests an ocean-island tholeiite (OIT) signature. The low-K tholeiitic, OIT-like character implies an intraplate oceanic mantle source contribution to basalt generation and provides quantitative constraints for refining regional tectonic reconstructions of Central Sulawesi during emplacement of the Taopa volcanic unit.